2012
DOI: 10.1590/s1983-51752012000100024
|View full text |Cite
|
Sign up to set email alerts
|

Rotina de treinamento laboratorial em microcirurgia do Instituto Nacional do Câncer

Abstract: Microsurgery is a technique in which the surgery is performed under optical magnification in vessels with a diameter of less than 3 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…2,4,11 Another relevant fact related to this method is that the handling techniques and skills acquired can be applied to other suture techniques, such as intestinal anastomoses; although it is unlikely to be possible to achieve the two suture layers generally used in this type of anastomosis. 12 One of the limitations of using these vegetable models is that an objective assessment cannot be made of the quality of the distance between stitches, since, in contrast with in vivo models in which coagulation occurs between sutures, in the vegetable model there will always be leakage between sutures, so this cannot be used to determine whether the distance between stitches is correct. Nevertheless, these characteristics do not rule out using this model as an initial step in the learning curve of several aspects related to materials, threads and tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,11 Another relevant fact related to this method is that the handling techniques and skills acquired can be applied to other suture techniques, such as intestinal anastomoses; although it is unlikely to be possible to achieve the two suture layers generally used in this type of anastomosis. 12 One of the limitations of using these vegetable models is that an objective assessment cannot be made of the quality of the distance between stitches, since, in contrast with in vivo models in which coagulation occurs between sutures, in the vegetable model there will always be leakage between sutures, so this cannot be used to determine whether the distance between stitches is correct. Nevertheless, these characteristics do not rule out using this model as an initial step in the learning curve of several aspects related to materials, threads and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore believe that use of vegetables could be adopted for practicing vascular anastomoses and could be incorporated into residency and undergraduate medicine programs. 12 However, there are several improvements that need to be made to the model, such as assessing side-to-end anastomoses, and using it in dolls that simulate surgical procedures in greater detail and are connected to pulsating pressure systems. 4 It is therefore concluded that, of the models tested, yardlong beans exhibited the best characteristics for use in initial training in vascular anastomoses, because it has dimensions and consistency similar to human vessels and because of its resistance when tying surgical knots.…”
Section: Discussionmentioning
confidence: 99%
“…Following the basic rules during vessel or nerve preparation and suturing will always be the cornerstone of good practice in microsurgery. 14 The diameter of anastomosed vessels has become progressively smaller, with permeability rates greater than 95% in anastomosing a 1-mm-diameter vessel. 15 This is possibly due to the high quality of microscopes, improvements in instrument design, and improvements in surgical skills.…”
Section: Discussionmentioning
confidence: 99%
“…There are various training models involving different materials and animals. Some training routines have also been defined in order to obtain adequate vascular permeability and therefore success in daily practice 3 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…We attribute to this step the importance of learning how to manipulate and feel the delicacy of microvascular structures when performing dissection and microsuture without the presence of the stressor, which could occur initially in working with live animals. The latter are sensitive to many factors, such as small volume loss, prolonged surgical time and inadvertent injury by training without enough experience, easily causing animals death, which could increase the costs of training 3,4 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%